SOCIO-SPATIAL FRAGMENTATION IN MEDIUM-SIZED BARAZILIAN CITIES: trends and perspectives of the new urban condition in Mossoró/RN and Marabá/PA - Silva, Cleiton Ferreira da [UNESP] (Univ Estado Rio Janeiro, 2024)
Studies analyzing the impact of globalization and post-Fordism in Latin American cities have shown significant transformations to the shape and content of urban spaces. These phenomena have been referred to as socio-spatial fragmentation. The fragmentation of Brazil's socio-spatial environment has manifested itself through multiple events, which have been analyzed in several studies. Considering that debate, this paper aims to investigate some of the aspects, i.e. the emergence of new centralities on the outskirts of cities, the expansion of fortified housing on the suburbs aimed at people from the middle and upper classes in conjunction with affordable housing such as the PMCMV, and new segmented consumption practices such as shopping centres . This is why the idea is to characterize these changes in medium-sized Brazilian cities, as represented here by the cities of Marab & aacute; -PA and Mossor & oacute;-RN, using trade, service, consumer space and housing data and locations as well as fieldwork to obtain an analytical understanding of said phenomena. As such, this study is one of the initial results of a contemporary analysis into social and spatial fragmentation processes and the social division of urban space.
Keywords: socio-spatial fragmentation; medium-sized cities in Brazil; neoliberalism; globalization; inequalities